Studi Kasus : Gambaran Diri Pasien Amputasi Copart Prosthesis Akibat Trauma Kecelakan Untuk Pasien Amputasi Ankle - Nur Rachmat; Herawati Priangi (Poltekkes Kemenkes Padang, 2019)
Direct accidents are accidents that result in defects or damage to limbs that lead to amputation. While indirect accidents are accidents which cause one aspect of life to be disturbed, especially on economic and social aspects. Individuals who experience a traumatic event will experience different reactions whether they become worse with the conditions they experience or the individual is able to adjust to the conditions they face and rise from adversity or become strong in the face of these traumatic events. Adjustments that can make individuals able to return to normal life or become better. Copart Amputation, Copart Prosthesis, Polycentric Ankle Joint. These operating methods and techniques have not changed and are still widely used today. Copart prosthesis is an artificial foot used for amputation of the ankle. the process of making copart prosthesis includes assessment, measurement, casting, fabrication, fitting, finishing. Of all the components for copart patients, prosthetic is the most important component that can have an effect on the stability of the road pattern. Options for panel opening type design made from polypropylene or most often GRF laminated (glas reinforeced plastic). the ancient type of postesis is made of sponges and skin.